Enhancement of waste heat collection using phase change material - Lim, Thaddeus Kuo Jiang (Nanyang Technological University, 2024)
The energy crisis of 21st century can be tackled using Phase Change Material acting as Latent Heat Storage System (LHTESS). Paraffin wax is commonly used but suffers from low thermal conductivity, as such heat transfer improvement methods is required. This report comprises of both experimental and numerical study of a double pipe in shell LTHESS using RUBITHERM RT 42 paraffin wax as Phase Change Material. Parameter study investigates the heat transfer improvement methods using eccentricity, counter-flow configuration and also the performance during simultaneous charging and discharging. The matching study between experiment and simulation had acceptable results, which validated the simulation model settings and the following simulation results from parameter studies. The simulation cases use the same parameters other than the geometry dimensions for group 1, heat transfer fluid (HTF) flow direction for group 2 and HTF temperature configuration for group 3. The analysis of results is based on melting/solidifying fraction and time taken. The numerical simulations in parameter studies found that increasing top pipe eccentricity can improve discharging process as it reduces solidifying time by up to 17.68%. Similarly, increasing bottom pipe eccentricity during charging process reduces melting time by up to 38.04%. It is also found that counter-flow configuration provides slight enhancement for both charging and discharging process, reducing melting time by 3.5% and solidify time by 1.18%. During simultaneous charging discharging operations, the ideal configuration is to have hot HTF pipe at bottom and cold HTF pipe at the top, as it provides up to 38% improvement in melt fraction performance. Overall, the effect of natural convection is crucial in both charging and discharging process, affecting melting and solidifying time during operation.